2009
DOI: 10.1073/pnas.0901778106
|View full text |Cite
|
Sign up to set email alerts
|

ER-resident proteins PDR2 and LPR1 mediate the developmental response of root meristems to phosphate availability

Abstract: Inadequate availability of inorganic phosphate (Pi) in the rhizosphere is a common challenge to plants, which activate metabolic and developmental responses to maximize Pi acquisition. The sensory mechanisms that monitor environmental Pi status and regulate root growth via altered meristem activity are unknown. Here, we show that PHOSPHATE DEFICIENCY RESPONSE 2 (PDR2) encodes the single P 5-type ATPase of Arabidopsis thaliana. PDR2 functions in the endoplasmic reticulum (ER) and is required for proper expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
256
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(263 citation statements)
references
References 42 publications
5
256
2
Order By: Relevance
“…Current studies have suggested that this effect is, at least in part, associated with increased Fe accumulation in root meristems when plants are grown under low P (Hirsch et al, 2006;Ward et al, 2008;Zheng et al, 2009). In agreement with a possible Fe-induced repression of the PR under low P, it has been shown that PR elongation can be restored by lowering the Fe concentrations in the P-deficient medium (Ward et al, 2008;Ticconi et al, 2009). Despite being essential for plant growth and development, an overload of Fe can produce highly reactive hydroxyl radicals that have toxic effects in cells (Graf et al, 1984).…”
Section: The Effect Of Nutrient Availability On Root Lengthsupporting
confidence: 54%
See 1 more Smart Citation
“…Current studies have suggested that this effect is, at least in part, associated with increased Fe accumulation in root meristems when plants are grown under low P (Hirsch et al, 2006;Ward et al, 2008;Zheng et al, 2009). In agreement with a possible Fe-induced repression of the PR under low P, it has been shown that PR elongation can be restored by lowering the Fe concentrations in the P-deficient medium (Ward et al, 2008;Ticconi et al, 2009). Despite being essential for plant growth and development, an overload of Fe can produce highly reactive hydroxyl radicals that have toxic effects in cells (Graf et al, 1984).…”
Section: The Effect Of Nutrient Availability On Root Lengthsupporting
confidence: 54%
“…of PR elongation under low P has been associated with reduced cell elongation and the loss of cell division activity in the PR apical meristem (Sanchez-Calderon et al, 2005;Ticconi et al, 2009). Current studies have suggested that this effect is, at least in part, associated with increased Fe accumulation in root meristems when plants are grown under low P (Hirsch et al, 2006;Ward et al, 2008;Zheng et al, 2009).…”
Section: The Effect Of Nutrient Availability On Root Lengthmentioning
confidence: 98%
“…By contrast, the phosphate deficiency responses2 (pdr2) mutant displays a hypersensitive response of root meristems to Pi deficiency (Ticconi et al, 2004). The PDR2 gene encodes a P5-type ATPase that is localized in the endoplasmic reticulum and interacts with LPR1 genetically in mediating primary root growth under Pi deficiency (Ticconi et al, 2009). Auxin (López-Bucio et al, 2002;Nacry et al, 2005;Pérez-Torres et al, 2008), GAs (Jiang et al, 2007), and ethylene (Borch et al, 1999;Ma et al, 2003;Yu et al, 2012) are also involved in the control of Pi deficiency-mediated remodeling of RSA.…”
mentioning
confidence: 99%
“…PDR2 encodes an endoplasmic reticulum (ER)-localized P 5 -type ATPase (19). PDR2 and LPR1 have been proposed to orchestrate RAM exhaustion in a genetically interacting route under low-Pi conditions (19). Whereas the precise function of PDR2 has not been determined, LPR1 is essential for primary root inhibition under lowPi conditions and it has been shown to have ferroxidase activity (16,19,20).…”
mentioning
confidence: 99%
“…A mutant that is hypersensitive to low Pi, phosphate deficiency response 2 (pdr2), and triggers the root system response to low Pi availability faster that the wild type (WT) was also reported (18). PDR2 encodes an endoplasmic reticulum (ER)-localized P 5 -type ATPase (19). PDR2 and LPR1 have been proposed to orchestrate RAM exhaustion in a genetically interacting route under low-Pi conditions (19).…”
mentioning
confidence: 99%